2014
DOI: 10.1109/tvcg.2014.2346434
|View full text |Cite
|
Sign up to set email alerts
|

Conforming Morse-Smale Complexes

Abstract: Morse-Smale (MS) complexes have been gaining popularity as a tool for feature-driven data analysis and visualization. However, the quality of their geometric embedding and the sole dependence on the input scalar field data can limit their applicability when expressing application-dependent features. In this paper we introduce a new combinatorial technique to compute an MS complex that conforms to both an input scalar field and an additional, prior segmentation of the domain. The segmentation constrains the MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…A future direction is to consider the adaptability of the proposed approach to discrete MS complexes, which can be computed efficiently [29]- [35].…”
Section: Discussionmentioning
confidence: 99%
“…A future direction is to consider the adaptability of the proposed approach to discrete MS complexes, which can be computed efficiently [29]- [35].…”
Section: Discussionmentioning
confidence: 99%
“…While the authors presented a solution, the algorithm required a serial traversal, and is too slow for practical use for QTAIM analysis. Instead, in T opo MS , we utilize an approach that allows fast parallel computation of discrete gradient fields that also conforms to a prior labeling computed through numeric integration …”
Section: Related Workmentioning
confidence: 99%
“…The boundary map L is nonzero only for cells having vertices with different labels in scriptL. We use the algorithm proposed by Gyulassy et al In the following discussion, we denote a cell that has been identified as critical by pairing it with itself, e.g., α,α. Furthermore, a cell is assigned if and only if it has been identified as critical or paired in a discrete gradient vector.…”
Section: Topoms: Algorithmic Detailsmentioning
confidence: 99%
“…1). In many applications, persistence diagrams help users as a visual guide to interactively tune simplification thresholds in topology-based, multi-scale data segmentation tasks based on the Reeb graph [9,19,34,42,45] or the Morse-Smale complex [21,22]. Distance: In order to evaluate the quality of compression algorithms, several metrics have been defined to evaluate the distance between the decompressed data, noted g : M → R, and the input data, f :…”
Section: Data Given Anmentioning
confidence: 99%